2021
DOI: 10.3389/fonc.2021.738406
|View full text |Cite
|
Sign up to set email alerts
|

N6-Methyladenosine Methyltransferase METTL14-Mediated Autophagy in Malignant Development of Oral Squamous Cell Carcinoma

Abstract: N6-methyladenosine (m6A) is the most abundant internal mRNA modification in eukaryotes and is related to stability, localization, or translation efficiency in tumorigenesis. Autophagy plays an important role in the occurrence and development of tumours. However, the relationship between m6A and autophagy remains unclear. In this study, we used a rapamycin-induced autophagy model of oral squamous cell carcinoma (OSCC) cells, and observed increased m6A RNA methylation. When autophagy was activated, the methyltra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…METTL14 was downregulated and correlated with lymph node metastasis of CRPC and was negatively correlated with the Gleason grade in PCa [ 130 ]. METTL14 was downregulated in triple-negative breast cancer (TNBC) [ 118 ], esophageal cancer (EC) [ 131 ], gastric cancer [ 132 ], osteosarcoma (OS) [ 133 ],Wilms tumor, [ 134 ] and oral squamous cell carcinoma (OSCC) [ 135 ], and low METTL14 expression was related to poor prognosis. Notably, it has been confirmed that METTL14 knockout can activate Wnt and PI3K-Akt signals to promote the growth and invasion of gastric cancer cells [ 132 ].…”
Section: Introductionmentioning
confidence: 99%
“…METTL14 was downregulated and correlated with lymph node metastasis of CRPC and was negatively correlated with the Gleason grade in PCa [ 130 ]. METTL14 was downregulated in triple-negative breast cancer (TNBC) [ 118 ], esophageal cancer (EC) [ 131 ], gastric cancer [ 132 ], osteosarcoma (OS) [ 133 ],Wilms tumor, [ 134 ] and oral squamous cell carcinoma (OSCC) [ 135 ], and low METTL14 expression was related to poor prognosis. Notably, it has been confirmed that METTL14 knockout can activate Wnt and PI3K-Akt signals to promote the growth and invasion of gastric cancer cells [ 132 ].…”
Section: Introductionmentioning
confidence: 99%
“…The formation of complexes reduces the chemosensitivity of bladder cancer to chemotherapeutic agents [ 261 ]. METTL14 directly binds to eIF4G1 mRNA and reduces the stability of eIF4G1 RNA by mediating m 6 A modification, thereby regulating autophagy levels and effectively reducing the growth of oral squamous cell carcinoma [ 262 ]. METTL16 is an RNA methyltransferase primarily responsible for the deposition of N6-methyladenosine (m 6 A) in transcripts.…”
Section: Rna Modificationsmentioning
confidence: 99%
“…m 6 A methyltransferase is involved in the development of cancers. Several studies have indicated that METTL3 and METTL14 are closely associated with cancer cell proliferation, the epithelial to mesenchymal transition (EMT) process and autophagy, and are essential genes to regulate intracellular activities (38)(39)(40)(41)(42)(43).…”
Section: Rna Modification and M 6 Amentioning
confidence: 99%
“…YTHDF2 is related to autophagy and metastasis, IGF2BP1 is involved in the metastasis process of cancer cells and IGF2BP2 has a vital role in autophagy and proliferation. HNRNPC and HNRNPA2B1 promotes the EMT process (20,39,41,(54)(55)(56)(57).…”
Section: Rna Modification and M 6 Amentioning
confidence: 99%
See 1 more Smart Citation